Analysis of Cost of Production Using the Full Costing Method in Printing Business of Diplomas Map - Anisa Nur Lela Sari (NAROTAMA UNIVERSITY, Indonesia, 2022)
CV. Aneka Usaha is a company in the printing sector that produces diploma maps starting from school base to universities that have problem h price tree production . Cost of goods production on CV. Various businesses are classified as simple which include: cost ingredient raw , energy work , and electricity costs the calculation is considered less right because not yet enter all elements price tree in- house production his efforts . Study this aim . Study this aim for knowing how price tree production use method full costing in the diploma map printing business . Study this use method qualitative and technical data collection used are primary and secondary . Techniques used is data analysis . Research results this show that price tree production using full costing get score tall compared with company , according to full costing price tree production in 2019 Rp . 30,924,350/ month , in 2020 Rp. 18,949,800/ bu , in 2021 Rp. 24,067,950/ month , Increase and decrease the full costing value is caused amount production at the company no always stable every year , while method company year 2019 Rp. 30,541,350, in 2020 Rp. 18,825,300, in 2021 Rp. 23,581,950. Suggestions given for CV. Various Businesses, companies should To do calculation to elements price tree production by complete so that could knowing score price tree in- house production company .